BLOOD DONATION APP (BLOODO) - ANIS SYAFIKAH, MOHD YUSRI (Universiti Malaysia Sarawak (UNIMAS), 2019)
Human needs blood to live and there is no substitute for it. The Blood Donation App (BlooDo) is aimed to design and develop an application that will help in giving easier way for the blood donor in donating blood. The BlooDo app has features like notify the user when there is any blood donation event nearby, keep track of the previous date of donating blood and register as a blood donor via online. This application can help by notifying the user when there is any blood donation event happened nearby. With the help of this application, the donors can manage and plan their time well whenever they want to donate blood. This application will be installed on smart devices (android).